بازاڕ و کاروانسەراکانی شارەکانی باشوری کوردستان لەسەدەی نۆزدە (توێژینەوەی هەڵێنجراو) (Sulaimani Journal for Humanities, 2023)
Markets and Khans are considered the most important commercial centers where Merchants and Travelers meet, where commercial transactions take place and providing them with everything they need and their animals to eat, drink, and rest. the Kurdish cities in the southern Kurdistan included many Markets and Khans, especially at the end of the nineteenth century , these Khans were among the reasons for its commercial and agricultural renaissance as well as an architectural facade, these places are not only commercial center in which commercial deals concluded, but rather they are considered a cultural club where travelers and merchants from different countries and cultures meet and talks about the social and cultural situation of their countries. These markets and khans are historical and cultural landmarks that some of which have disappeared. The research consists three axes, the first axes talk about the defienition of the city and the borders of southern Kurdistan, the second axes talks about Markets in Kurdish cities in the southern Kurdistan and their specialization as far as commercial goods dealt with to the city Markets. The third axes talk about the khans and the social servies they provided to Merchents and travelers.
Keywords: Markets; Khans; Kurdish cities; southern Kurdistan)